Analisis Pengaruh Kualitas Produk Terhadap Loyalitas Pengguna Handphone Xiomi di Samarinda - Siti Nurhasanah; Syachrul Syachrul; Dyah Kusrihandayani; Santa Awregas (Politeknik Negeri Samarinda, 2021)
This study aims to determine whether there is a significant effect between product quality on the loyalty of Xiaomi mobile users in Samarinda. The population in this study were Xiaomi mobile phone users in Samarinda. With the specified number of respondents as many as 50 respondents. The sampling technique used is Accidental Sampling. The test in this study uses the SPSS version 24 program tool. The analysis and hypothesis testing tools used are validity test, reliability test, normality test, simple linear regression test, partial test (T) and coefficient of determination test (R2). From the results of the study, it shows that product quality has a significant effect on the loyalty of Xiaomi mobile users in Samarinda. The results of the study for product quality on user loyalty partially or t test obtained t count, which means t count (6.446 > 1.677) with a significance level (0.000 < 0.05). So the hypothesis that states can be accepted. The influence of the coefficient of determination (R2) product quality has an effect on the loyalty of Xiomi cellphone users in Samarinda. It can be seen from R = 0.681, meaning that there is a strong relationship, while R Square is 0.464 which means 46.4% this shows that the independent variable (product quality) can affect the dependent variable (user loyalty), while the rest can be explained by the variables other variables not examined in this research. So the hypothesis that the coefficient of product quality determination has a positive effect on user loyalty.